2020
DOI: 10.7150/jca.32850
|View full text |Cite|
|
Sign up to set email alerts
|

Depletion of CDC5L inhibits bladder cancer tumorigenesis

Abstract: Cell division cycle 5-like (CDC5L) protein is a cell cycle regulator of the G2/M transition and has been reported to participate in the catalytic step of pre-messenger RNA (mRNA) splicing and DNA damage repair. Recently, CDC5L was also found to act as a candidate oncogene in osteosarcoma and cervical tumours. However, the role of CDC5L expression in bladder cancer remains unclear. Here, we analysed the expression and clinical significance of CDC5L in bladder cancer tissues. The expression of CDC5L in fresh bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
(23 reference statements)
2
29
0
Order By: Relevance
“…In bladder cancer, CDC5L expression was obviously increased and CDC5L expression was significantly related to pathology grade and Ki67 expression in bladder cancer. Furthermore, CDC5L inhibition suppressed proliferation, migration, invasion and EMT while induced apoptosis of bladder cancer cells [26]. Here, we have confirmed that CDC5L interference can effectively inhibit the promotion effects on proliferation and cell cycle induced by ANXA7 overexpression.…”
Section: Discussionsupporting
confidence: 70%
“…In bladder cancer, CDC5L expression was obviously increased and CDC5L expression was significantly related to pathology grade and Ki67 expression in bladder cancer. Furthermore, CDC5L inhibition suppressed proliferation, migration, invasion and EMT while induced apoptosis of bladder cancer cells [26]. Here, we have confirmed that CDC5L interference can effectively inhibit the promotion effects on proliferation and cell cycle induced by ANXA7 overexpression.…”
Section: Discussionsupporting
confidence: 70%
“…The depletion of CDC5L leads to the inhibition of mitotic progression, and it induces mitotic failure [80]. Additionally, the downregulation of CDC5l inhibits the proliferation of bladder cancer cells [81]. ANLN has been experimentally proven to interact with CDC5L [82].…”
Section: Other Binding Partnersmentioning
confidence: 99%
“…A previous study found that Cdc5L is a regulator of mitotic progression as a pre-mRNA splicing factor. The deletion of endogenous Cdc5L decreases cell viability via dramatic mitotic arrest [ 29 ], which has not been reported in plants, but has been widely studied in animals, especially in the proliferation of cancer cells [ 30 ]. Cdc5L is also essential for porcine oocyte maturation [ 31 ].…”
Section: Resultsmentioning
confidence: 99%